Examining the economic impact of foreign students in public Universities on Singapore economy in 2010 and foreign students' pre-trip decision making factors - Lim, Kelly Kaili (2011)
This paper aims to provide insights into the growing yet under-studied education tourism segment in Singapore. The objective of this paper is two-fold: to quantify the economic impact of the foreign students‟ expenditure in Singapore and to analyze the various pre-trip decision making factors of foreign students in choosing an education destination.